THE REGION’S R&D PASSPORT AS INSTRUMENT OF STATE POLICY - Anna Vital’evna Zolotukhina (Science and Innovation Center Publishing House, 2016)
The article is devoted to studying of opportunities to increase of the state research and development (R&D) policy’s efficiency in the region on the basis of its information support’s improvement. Allowing to stimulate R&D in the region tools and measures, capable to provide development of scientific and technical capacity of the Russian Federation and its subjects are necessary in modern conditions. The region’s scientific and technical passport of the which formation assume to use of data presentation for development of science, equipment and technology’s unified system in each country’s regionone of such tools is capable to become. Its introduction within monitoring scientific and technical capacity’s parameters in the Russian regions will effectively carry out R&D analysis and evaluation at the territorial level, to conduct interregional comparisons, track the changes with a view to the quality decision-making in the field ofregionalscience and technology policy. Purpose: development of information support’s tools of the state R&D policy in the region. Methods and/or methodology: in article the research methods literature review, retrospective analysis and also statistical methods of the analysis were used. Results: developed the content of the region’s technical and scientific passport, testing of which is shown on an example of one of Russia’s regions(the Republic of Bashkortostan). Practical implications: the results can be applied federal and sub-federal government in order to improve the monitoring scientific and technological capacity’s efficiency at justification of the state R&D policy’s directions and measures.